2015
DOI: 10.1371/journal.pone.0142717
|View full text |Cite|
|
Sign up to set email alerts
|

Isolation, Biochemical and Molecular Identification, and In-Vitro Antimicrobial Resistance Patterns of Bacteria Isolated from Bubaline Subclinical Mastitis in South India

Abstract: Buffaloes are the second largest source of milk. Mastitis is a major impediment for milk production, but not much information is available about bubaline mastitis, especially subclinical mastitis. The aim of this study was to (a) investigate the application of various tests for the diagnosis of bubaline subclinical mastitis, (b) identify the major bacteria associated with it, and (c) evaluate the antibiotic resistance pattern of the bacteria. To this end, 190 quarter milk samples were collected from 57 domesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
59
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(71 citation statements)
references
References 61 publications
10
59
2
Order By: Relevance
“…This low percentage was because of good milking practices and use of teat dips before milking. While, another study by Preethirani et al (2015) showed high percentage (9.8) of E. coli isolates from an unorganized dairy farm. These results were not in accordance to present study.…”
Section: Resultsmentioning
confidence: 93%
“…This low percentage was because of good milking practices and use of teat dips before milking. While, another study by Preethirani et al (2015) showed high percentage (9.8) of E. coli isolates from an unorganized dairy farm. These results were not in accordance to present study.…”
Section: Resultsmentioning
confidence: 93%
“…The most frequently isolated pathogens are Staphylococcus aureus, Escherichia coli, Klebsiella spp., Streptococcus spp., Mycoplasma spp., Enterobacter spp., Bacillus spp., and Corynebacterium species (Abebe et al, 2016;Gao et al, 2017;Hoque et al, 2018). Therefore, the accurate identification of pathogens that cause CM enables appropriate choices for antimicrobial treatment and preventive mastitis management (Preethirani et al, 2015;Van Boeckel et al, 2015;Cheng et al, 2019). Over the past two decades, a wide range of phenotyping and genotyping methods have been implemented to study mastitis-causing bacteria (Preethirani et al, 2015;Gao et al, 2017;Hoque et al, 2018;Cheng et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the accurate identification of pathogens that cause CM enables appropriate choices for antimicrobial treatment and preventive mastitis management (Preethirani et al, 2015;Van Boeckel et al, 2015;Cheng et al, 2019). Over the past two decades, a wide range of phenotyping and genotyping methods have been implemented to study mastitis-causing bacteria (Preethirani et al, 2015;Gao et al, 2017;Hoque et al, 2018;Cheng et al, 2019). Although culture-based techniques are traditionally used to detect CM bacteria, these methods are time-consuming and have the inherent drawback of not being applicable to non-cultivable bacteria (Baron et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Bovine mastitis is one of the major problems facing the dairy industry worldwide (Benić, Habrun, & Kompes, 2012;Elbehiry, Al-Dubaib, Marzouk, Osman, & Edrees, 2016;Preethirani et al, 2015). Several bacterial species are responsible for bovine mastitis infections, Staphylococcus aureus (S. aureus) being one of the most prevalent mastitis pathogens, causing the most virulent forms of bovine mastitis (El Behiry, Schlenker, Szabo, & Roesler, 2012;Yang et al, 2008).…”
Section: Introductionmentioning
confidence: 99%